Combination Of Financial Decision And Profitability And Its Effect On Company Value Registered In Indonesia Stock Exchange Year 2010-2015 - Irdiana, Sukma (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2017)
The purpose of this study was conducted to determine the significant effect between profitability, investment decisions, funding decisions and dividend policy on corporate value. And to know the effect simultaneously between profitability, investment decisions, funding decisions, and dividend policy on corporate value. research approach used in this research is quantitative approach. The population in this study are all companies that are members of the BLUE CHIPS stock group listed on the Indonesia Stock Exchange from 2010-2015. Sample selection method used is purposive sampling and analysis model used is multiple linier regression analysis. The results show that partially Profitability (ROA), Investment Decision (PER), and Decision Funding (DER) that does not affect the value of the company. While the dividend policy (DPR) affects the value of the company. Simultaneously, the result of the research shows that there is a significant influence between Profitability (ROA), Investment Decision (PER), Fund Decision (DER), and Dividend Policy (DPR) to Company Value (PBV). While the R Square value of 0389 or 38.9% indicates that the contribution of the influence of profitability (ROA), Investment Decision (PER), Funding Decision (DER), and Dividend Policy (DPR) to Company Value (PBV) of 38.9% and the balance of 61.1% influenced by other variables not included in this study.